2018
DOI: 10.1161/atvbaha.118.310839
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Glycocalyx as a Shield Against Diabetic Vascular Complications

Abstract: The endothelial glycocalyx (EG), which covers the apical surface of the endothelial cells and floats into the lumen of the vessels, is a key player in vascular integrity and cardiovascular homeostasis. The EG is composed of PGs (proteoglycans), glycoproteins, glycolipids, and glycosaminoglycans, in particular hyaluronan (HA). HA seems to be implicated in most of the functions described for EG such as creating a space between blood and the endothelium, controlling vessel permeability, restricting leukocyte and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
134
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(138 citation statements)
references
References 178 publications
0
134
0
4
Order By: Relevance
“…SDC4 carries HS side chains so HS shedding is likely to accompany SDC4 shedding as we have shown previously in vitro 16 and others have shown in vivo in a diabetes model. 55 Glycocalyx component hyaluronan 56 has also been shown to be shed in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…SDC4 carries HS side chains so HS shedding is likely to accompany SDC4 shedding as we have shown previously in vitro 16 and others have shown in vivo in a diabetes model. 55 Glycocalyx component hyaluronan 56 has also been shown to be shed in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that endothelial mechanotransduction signalling pathways participate in generation of redox signals that affect inflammation status of cells . However, to this date, the actual intermediate signals of flow‐induced, shear stress–related mechanotransduction have not been elucidated, and the role of EG in this regard is unresolved . What is known is that enzymatic degradation of the EG constituents decreases flow‐induced nitric oxide (a vasoregulating agent responding to shear stress changes) production, confirming that EG plays an important role in such signal transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this protective coating is very similar to the brain's interstitial extracellular matrix in molecular contents, which is difficult to examine by ultrastructure imaging due to its extreme thinness even at very high magnification due to the tightly packed glia and neurons within a confined space created by the exoskeleton the skull. The elusive ecGCx is in a constant state of flux and also in a constant state of being regenerated and repaired by the endothelium and plasma constituents[63,64,65,66]. The systemic cells and molecules of the blood seldom see or come into direct contact with the plasma membrane-plasmalemma of the EC, because it is constantly and nearly continuously covered by the protective ecGCx surface coating, which prevents direct exposure of systemic blood components to the EC plasma membrane in health.…”
mentioning
confidence: 99%